2016
DOI: 10.1186/s12888-016-0974-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high use of general practitioner and psychiatrist services among patients attending an addiction rehabilitation center

Abstract: BackgroundThis study aimed to 1) identify the characteristics of individuals with substance use disorders (SUDs) who make high use of services provided by general practitioners (GP) and psychiatrists while receiving services concurrently from an addiction rehabilitation center (ARC), and 2) to compare high service users to moderate and low service users.MethodsData were compiled for 4,407 individuals with SUDs who were receiving services from an ARC in 2004. The data came from the merging of four databases: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
4
0
2
Order By: Relevance
“…It is possible that these users require concerted action involving multiple health professionals; the strong correlation between these two user profiles is well documented in the literature. UPDs were identified as more likely to be high users of healthcare services, including primary care and specialized services [ 55 57 ]. A covariance emerged between network integration strategies and high users, but not between these strategies and UPDs.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these users require concerted action involving multiple health professionals; the strong correlation between these two user profiles is well documented in the literature. UPDs were identified as more likely to be high users of healthcare services, including primary care and specialized services [ 55 57 ]. A covariance emerged between network integration strategies and high users, but not between these strategies and UPDs.…”
Section: Discussionmentioning
confidence: 99%
“…En revanche, même si ces individus ne consultent pas spécifiquement pour un TLS, ils demeurent néanmoins en contact avec le système médical. À titre d'exemple, 98 % des usagers du Centre de réadaptation en dépendance de Montréal, qui offre principalement des services psychosociaux, avaient eu minimalement un contact avec un médecin au cours des deux années à l'étude 57 . Ainsi, les cas non identifiés relèvent davantage d'aspects administratifs (code non posé, code alternatif à celui d'un TLS) que d'une faible demande de services de la part des usagers ou de négligence professionnelle médicale (c.-à-.d.…”
Section: Discussion Et Conclusionunclassified
“…Sub-model 4 revealed that more needs were positively associated with recovery when mediated by the use of food banks; yet, when mediated by number of MH professionals consulted, the relationship between total number of needs and recovery became negative. This result suggests that seeking help from multiple sources, as commonly occurs among heavy service users (Huỳnh, Ngui, Kairouz, Lesage, & Fleury, 2016), implied a lack of continuity of care and of individualized treatment planning, both antithetical to recovery-oriented service delivery (Tandon, Targum, Nasrallah, & Ross, 2006).…”
Section: Discussionmentioning
confidence: 99%